Evaluation of Glyphosate Adsorption Process in Aqueous Solutions on Fe(III) - Impregnated Bentonite and Kaolinite (2023)
Glyphosate is a widely used herbicide, however, its detection in water is an environmental problem due to its character as an emerging pollutant. The advanced oxidation processes - AOP are used for its degradation on materials modified with iron. In this study, the adsorption and catalytic degradation capacity of glyphosate was evaluated using bentonite and kaolinite impregnated with iron. The impregnated materials were characterized by X-ray diffraction (XRD), X-ray fluorescence (XRF), and scanning electron microscopy (SEM), to determine structural changes, monitoring of incorporated iron content, and morphological changes, respectively. Subsequently, adsorption tests were carried out using aqueous glyphosate solutions in a concentration range between 12-27 mg/L of glyphosate, using UV-Vis spectroscopy for their quantification, the results showed that both bentonites and kaolinites impregnated with iron reached up to 55 % adsorption of the herbicide. Analysis by FT-IR showed that the impregnated bentonites after the adsorption process exhibit chemical interactions with the herbicide. The catalytic tests revealed that the materials used in this work and under the tested measurement conditions present a degradation percentage of up to 34%.